133 PT1-T2 N0 M0 breast cancer with early reccurence. (18th September 2019) - zemni, I; Haddad, S; Adouni, O; Saadallah, F; Ben hassouna, J; Hechiche, M; chargui, R; Rahal, K
Abstract : Objectives: Node-negative breast cancer patients have a low likelihood of cancer recurrence, and are often referred to as low-risk cancer patients. However some of these patients wil experience early reccurence (within the first two years). Therefore, it is important to identify breast cancer traits that may predict the risk of recurrencein this subgroup. Methods: We retrospectively reviewed 331 female patients with pT1-T2 N0 M0 breast cancer treated in Salah Azaiez Institute from 2001 to 2003, among them 64 patients (19.3%) experienced reccurence. Most of the patients presented an early reccurence (N=57) within the first two years. Results patients, and lymphovascular invasion (LVI) ratio were% 66.2, 46.8% and 10.6%, respectively. Estrogen receptor and progesterone receptor positivity were 46.9% and 41.9%. Breast conserving surgery was performed in 47% of cases (N=156) versus 53% (N=175) of patey type surgery. Overall survival at 3 and 5 years were respectively 83.7% and 68.2%. Univariate analysis showed that only radiation therapy had a significant influence on OS. Disease free survival at 3 and 5 years were 87.9% and 82.2%. On univariate analysis, tumor Grade and hormonal traitement appeared as the only factors to influence DFS. Conclusions: The results of this retrospective study shows that even in pT1-T2 N0M0 tumors, the risque of early reccurence is important and this population should benefit from a close follow-up, especially in some selected cases.